Performance of contiguous pile wall for deep excavation on Chao Phraya River Bank. - Teparaksa, Wanchai (Asean Engineering Journal)
The excellent medical center in Asia, Siriraj Hospital is the largest medical center in Asia is constructed with three basement floors on Chao Phraya River bank and close to the preserved building seated on shallow foundation. The excavation is about -10.85 m. depth below ground surface. The contiguous pile wall was used as the temporary soil protection system and permanent wall with two layers of temporary steel bracing system. The behaviour of contiguous pile wall was predicted by Finite Element Method (FEM) with simulation of all construction sequences. The instrument including inclinometer, tiltmeter, piezometer and ground surface settlement were installed in the contiguous pile, preserved builiding and in the ground, respectively. The performance of the contiguous pile wall was evaluated by instrumentation monitoring compared with FEM analysis and trigger level.